Urban Comprehensive Carrying Capacity and Development Order: A “Pressure-Capacity-Potential” Logical Framework - Li, Bingqian; Guan, Mei; Zhan, Lingyun; Liu, Chunqiang; Zhang, Zhipeng; Jiang, Huailong; Zhang, Yong; Dong, Guanglong (Frontiers in Environmental Science, 2022)
Urban comprehensive carrying capacity determines the scale and development direction of a city and is an important factor in the optimization of main function areas, the arrangement of urban development order, and the demarcation of urban development boundaries in China’s new national spatial planning system. Using the constructed "pressure-capacity-potential" model as a theoretical basis, this paper combines human factors and natural factors and calculates the urban carrying capacity index by means of multi-factor weighted summation, graded assignment, stepwise correction, and subsection variable weight. From the perspective of the integration and coordination of "three forces", urban development rules are established, and an urban development order based on the framework of "three districts and six types" is put forward. The results reveal four key findings. First, the "pressure-capability-potential" conceptual model analyzes the urban carrying capacity from the perspective of the integration of externality and internality, which can effectively support the orderly arrangement and rational layout of urban development. Second, the urban carrying pressure of Shandong province is general, and the urban carrying capacity is high. The results also showed that the urban carrying potential is low and the urban comprehensive carrying capacity is high. Third, in the "3+6" urban development pattern of Shandong Province, priority development and key development zones are the main areas. For the most part, these zones are distributed in the Jiaodong Peninsula, the Jinan-Taian-Jining development zone, and the surrounding areas of Weifang, Linyi, Liaocheng, and Heze. Moderate development zones are concentrated in Nansi Lake and the Yellow River Delta. Fourth, the urban development in Shandong province is mainly restricted by landform, water resources, environmental capacity, and geological disasters. Under the premise of ensuring resource conservation and environmental friendliness, using policies and engineering measures to revitalize stock space is an effective way to foster urban development in the 14th Five-Year Plan period.